BACTERIA CAUSED SEPSIS BIOMARKERS - Tjempakasari, Artaria; Nasronudin, Nasronudin (Indonesian Journal of Tropical and Infectious Disease, 2014)
Sepsis is a clinical condition of patients with serious infections that show a systemic inflammatory response, with or without a positive blood culture. sepsis is one of the most frequent causes of death in patients in intensive care units. We are at urgent need for biomarkers and reliable measurements that can be applied to risk stratification of septic patients and that would easily identify those patients at the highest risk of a poor outcome. Such markers would be of fundamental importance to decision making for early intervention therapy. Pro-inflammatory cytokines such as tumor necrosis factor-ï¡ (TNF- ï¡), interleukins-1,-6,-8 (IL-1, IL-6, IL-8) are postulated to play a major role in the pathogenesis of the syndrome. C-reactive protein (CRP) and procalcitonin (PCT) are among a few biomarkers thatincorporated into clinical practice although their precise role in the pathopysiology of sepsis and organ dysfunction still unclear.